EFEKTIVITAS PEMBERIAN TABLET FE DAN TABLET FE KOMBINASI VITAMIN C TERHADAP KADAR HB IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS KLAMBIR V KEBUN KEC. HAMPARAN PERAK TAHUN 2018 - Tri Marini; Nurul Ditta Amanda (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
One of the causes of iron deficiency anemia is the lack of adequate food intake for Fe sources and iron absorption with Vitamin C combination. The aim is to determine the effectiveness of giving fe tablets and combination tablets of vitamin C to hb levels at post partum mother at the working area of Klambir V community health care of Hamparan Perak sub district 2018. Quasy experimental research method with Two Group design pre-test and post-test. The population is all postpartum mothers. Sample of 20 peoples using purposive sampling. The statistical test used was the independent sample t test. The results showed that the average initial Hb level in postpartum mothers before consuming Fe was 10.51 g / dl after 4 weeks with an increase in Hb levels of 0.60 g / dl. In the intervention group, the mean initial Hb level was 10.46 g / dl. The average increase in Hb levels was g / dl in 4 weeks. The results of statistical tests showed that there was effectiveness in the administration of a combination of Vitamin C tablets with Hb levels in postpartum mothers with a p value of 0.000 (p <0.05). There was a significant effectiveness with the administration of a combination of vitamin C and Fe tablets to Hb levels in postpartum mothers. It is better to administer Fe tablets accompanied by vitamin C to help increase Hb levels